Integrated or separated: Voicing Indonesian EFL teachers’ and student-teachers’ preferences in teaching grammar - Hidayatulloh, Sibakhul Milad Malik; Margana, Margana (Englisia Journal, 2022)
This research aimed at exploring the teachers and student-teachers’ views on teaching grammar and their preferences. Indeed, recognizing the teachers and student-teachers’ views on teaching grammar and their preferences become a worthy source in constructing and providing the effective teaching grammar. This research invited twelve participants consisting of six high school teachers and six student-teachers from English department. A descriptive qualitative research design using an in-depth interview was applied to find out their views and preferences. The findings revealed that between teachers and student-teachers had same views on valuing the terms of grammar. However, they opposed each other on viewing the teaching grammar process. In terms of their preferences in teaching grammar, both teachers and student-teachers had same tendencies in which grammar must done by applying integrated teaching grammar approach. By using the findings of this research, some implications for teachers were also stated to develop the integrated grammar teaching process within the classroom setting.